Circumpolar mid-winter thaw and refreeze based on fusion of Metop ASCAT and SMOS, 2011/2012 - 2021/2022 - Bartsch, Annett; Bergstedt, Helena; Pointner, Georg; Muri, Xaver; Rautiainen, Kimmo (Zenodo, 2023)
Rain-on-Snow (ROS) events occur across many regions of the terrestrial Arctic in mid-winter. Snow pack propertiesare changing and in extreme cases ice layers form which affect wildlife, vegetation and soils beyond the duration of the event. Active and passive microwave data have been combined to identify events over land North of 65°N (Bartsch et al. 2023). In a first step Metop ASCAT (C-Band radar) was used to identify potential sudden snow structure change. In a second step, results have been masked for coincident observation of wet snow within +- 3 days based on SMOS (derived from Centre Aval de Traitement des Données SMOS (CATDS) level 3 product). Note that the SMOS retrievals can havedata gaps due toradio frequency interferences(RFI) what leads to gaps in the event detection. The dataset is structured bycentre points of the hexagonal grid of the used Metop ASCAT product (EUMETSAT, approximately 12.5 km nominal resolution). Attributes include point ID (GPI), latitude, longitude and aggregated number of events for the months November to February, 2011/12 to 2021/22, and theirsum per winter (referred to as annual), or in case of daily results (date in file name)the magnitude of ASCAT backscatter change in dB (DSigma0; no data value is '0.0'). The dataset extents Seawinds QuikScat (Ku-band) based results for 2000-2009 (Bartsch 2010, Freund and Bartsch 2020). The study has received funding under the European Union's Horizon 2020 Research and Innovation Programme under Grant Agreement No. 869471 (CHARTER). This work was further supported by the European Space Agency CCI+ Permafrost project.